Welfare Reform and Migrant's Long-Term Labor Market Integration - Johannes S. Kunz; Anna Zhu (Institute of Labor Economics (IZA), 2023)
We study the effect of reducing welfare assistance on migrants# long-term integration in Australia. The policy postponed a migrant's eligibility for benefits during their first two years in the country. It mainly affected mothers and was announced after their arrival. Using a regression discontinuity design and 21 years of administrative welfare data, we find significant reductions in welfare receipt, where the gap widened over time, and stabilized in the long run. Benefit receipt amounts reduced by 28%, and time-on-benefits by 19%, particularly in the unemployment and disability categories. We observe larger treatment effects for mothers from disadvantaged backgrounds.
Keywords: E64; I30; J60; 330; welfare reform; labor market outcomes; migration; job quality